2022
DOI: 10.1038/s41598-022-07327-9
|View full text |Cite
|
Sign up to set email alerts
|

Small brains predisposed Late Quaternary mammals to extinction

Abstract: The Late Quaternary witnessed a dramatic wave of large mammal extinctions, that are usually attributed to either human hunting or climatic change. We hypothesized that the large mammals that survived the extinctions might have been endowed with larger brain sizes than their relatives, which could have conferred enhanced behavioral plasticity and the ability to cope with the rapidly changing Late Quaternary environmental conditions. We assembled data on brain sizes of 291 extant mammal species plus 50 more that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…However, brain size has also predicted how successful mammals were when introduced to novel environments, with higher rates of success in larger brained animals [ 3 ]. Further, increased brain size is connected to increased urban tolerance in birds [ 9 ] and a recent study even showed that larger brained animals were more likely to survive an extinction wave in the Late Quaternary (approximately 115 ka–500 years ago) [ 7 ]. For an invasive species such as the American mink, quickly adapting aspects of the body and brain to a new environment may provide major advantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, brain size has also predicted how successful mammals were when introduced to novel environments, with higher rates of success in larger brained animals [ 3 ]. Further, increased brain size is connected to increased urban tolerance in birds [ 9 ] and a recent study even showed that larger brained animals were more likely to survive an extinction wave in the Late Quaternary (approximately 115 ka–500 years ago) [ 7 ]. For an invasive species such as the American mink, quickly adapting aspects of the body and brain to a new environment may provide major advantages.…”
Section: Discussionmentioning
confidence: 99%
“…If and how much brain size matters for the evolutionary success of a species remains hotly debated [1][2][3][4][5][6][7][8]. To better understand the role of brain size linked to cognition, survival and evolutionary success, it is thus important to follow the evolution and flexibility of this trait.…”
Section: Introductionmentioning
confidence: 99%
“…The brain endocasts can provide pivotal insights into the evolution of sensation and cognition in extant and extinct carnivorans. Much of the focus has been on relative brain size, which correlates with diet [ 61 , 62 ], home-range size [ 63 ], problem solving ability [ 64 , 65 ], type of parental care [ 66 , 67 ], hibernation [ 68 ] and extinction risk [ 69 , 70 ]. Evidently, there is a plethora of forces involved in the evolution of the brain, but there have been few attempts to integrate these various factors into a broader understanding of what influences brain evolution [ 71 ].…”
Section: Overview Of Carnivoran Ecomorphologymentioning
confidence: 99%
“…For example, the capacities for climbing trees or burrowing on the ground offer partial escape routes from the environmental constrains unique to terrestrial living, selecting for generally longer lifespans compared to other terrestrial species (Bels & Russell 2023; Healy et al 2014Healy et al , 2019Mincer & Russo 2020;Withers et al 2016). Similarly, larger brains generally allows species to avoid hazardous situations, selecting for slower lives compared to other terrestrial representatives (Benson-Amram et al 2016;Bertrand et al 2022;Dembitzer et al 2022;González-Lagos et al 2010;Seyfarth & Cheney 2002). It becomes clear how a comprehensive understanding of mammalian adaptations across various environmental realms is crucial for unravelling the complexities of life history strategies.…”
Section: Introductionmentioning
confidence: 99%